Maharashtra, a profile : Vishnu Sakharam Khandekar felicitation volume - Khāṇḍekara, Vi. Sa. (Vishṇu Sakhārāma), 1898-1976; Bhāgavata, Acyuta Keśava (V. S. Khandekar Amrit Mahotsava Satkar Samiti, 1977)
Contributed articles on the cultural history of Maharashtra and Marathi literature.